A dynamical systems model of intrauterine fetal growth. Issue 6 (2nd November 2018) - Freigoun, Mohammad T.; Rivera, Daniel E.; Guo, Penghong; Hohman, Emily E.; Gernand, Alison D.; Symons Downs, Danielle; Savage, Jennifer S.
ABSTRACT: The underlying mechanisms for how maternal perinatal obesity and intrauterine environment influence foetal development are not well understood and thus require further understanding. In this paper, energy balance concepts are used to develop a comprehensive dynamical systems model for foetal growth that illustrates how maternal factors (energy intake and physical activity) influence foetal weight and related components (fat mass, fat-free mass, and placental volume) over time. The model is estimated from intensive measurements of foetal weight and placental volume obtained as part of Healthy Mom Zone (HMZ), a novel intervention for managing gestational weight gain in obese/overweight women. The overall result of the modelling procedure is a parsimonious system of equations that reliably predicts foetal weight gain and birth weight based on a sensible number of assessments. This model can inform clinical care recommendations as well as how adaptive interventions, such as HMZ, can influence foetal growth and birth outcomes.